2020
DOI: 10.1186/s12889-020-09103-8
|View full text |Cite
|
Sign up to set email alerts
|

Food supplements to reduce stunting in Pakistan: a process evaluation of community dynamics shaping uptake

Abstract: Background: There is an increasing interest in use of food supplements to prevent childhood stunting, however the evidence on the process indicators is scarce. We in this study explore the barriers to the effective implementation of food supplementation programs and the possible mitigation strategies which can guide the design of future programs. Methods: We undertook a process evaluation of a stunting prevention food supplementation pilot program in rural Pakistan that distributed Wheat Soy Blend (WSB) to pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…In addition to a lower average family income and a lower average mother’s education level, we found that older children and males had a greater risk of stunting or severe stunting than younger children and females did. These results are in line with those discovered in studies carried out in Indonesia as well as in other low- and middle-income nations [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition to a lower average family income and a lower average mother’s education level, we found that older children and males had a greater risk of stunting or severe stunting than younger children and females did. These results are in line with those discovered in studies carried out in Indonesia as well as in other low- and middle-income nations [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…Increased communication between health providers and rural households, either through incentives for providers to increase communication or through the employment of additional health providers such as community health workers, may increase salience and raise MNP adherence. Food supplementation programs in similar contexts have found success through meticulous planning focused towards improving health worker motivation, enhanced communication, and involvement of multiple stakeholders [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Zaidi (2020), in addition to soy, dietary supplements can also increase nutrition in pregnant women, reducing the stunting condition of children at birth. The findings suggest that some beneficiaries consume a total dose of the supplement, despite valuable knowledge among caregivers.…”
Section: Discussionmentioning
confidence: 99%